PRACTICE-ORIENTED TRAINING AS THE BASIS OF MULTILEVEL FORMING OF THE PROFESSIONAL GRAPHIC COMPETENCES - Vladimir I. Ivashchenko (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
He theoretical foundation of multi-level practice-oriented formation of professional graphic skills is presented. The paper contains the substantiation of the need for multi-level geometric-graphic preparation of saturated technological knowledge in the system, covering the period of study from secondary school to senior courses of a technical university. The features and conditions of realization of teaching graphic disciplines in modern conditions are distinguished. The technological nature of electronic geometric modeling, defining the creative nature of the learning activities of the pupils and students, is shown. Some patterns for basic geometrical graphic training in higher school associated with the need for adaptation of students are determined. The possibility and effectiveness of pre-university technological propedeutics based on electronic modeling in CAD / CAM software and the use of software-machine complex.